O Discurso do Projeto Político Pedagógico no ensino das relações étnico-raciais da Escola Jorge Travassos - CARMO, Maria da Conceição Ferreira do (2022)
main legislations for the teaching of Afro-Brazilian and indigenous history and culture, these being the law 10.639/2003 that amends the LDB/1996 that it includes the teaching of Afro-Brazilian and African history and culture and to articulate the teaching of Ethnic-Racial Relations with Law 11.645/2008, which makes the teaching of AfroBrazilian and indigenous history and culture mandatory. And that includes in the calendar the day of black consciousness as a mandatory commemorative date. In this sense, for the refinement of the research, documents such as the unified regiment of municipal schools in Capanema, State of Pará, are still used in the research. And the internal ordinance 003/2021 of the municipality, which consists of the main articles and laws for the teaching of Ethnic Relations in the schools of the municipality. A reading and analysis of the axes of the project was carried out, in which it was made available in a digitized version, in order to find the discourses of Ethnic-Racial relations, using the PPP and dialogue with authors who discuss the pedagogical political project and ethnic-racial relations. , the educational guidelines, together with laws 10.639/2003 and 11.645/2008 to analyze what they say about the teaching of cultures in school. The study is characterized as a qualitative research, of documentary character, the results obtained with the analyzes was the absence of treatment for the teaching of ethnic-racial relations in the pedagogical political project and in the curriculum for elementary and child education, the pedagogical document does not articulate proposals together with the laws 10.639/2003 and as for the law 11.645/2008 it is only mentioned in the project, with that the research identified that the project still does not contemplate the designations for the teaching of Ethnic-racial Relations nor the teaching of history and Afro-Brazilian and indigenous culture in its curriculum for Basic Education.